From Spark to Sculpture: A Practice-Based Exploration of Betta Fish Form Using Stainless Steel Rods - Santoso, Miky Endro; Tessa Eka Darmayanti (Institut Seni Indonesia Denpasar, 2025)
The development of three-dimensional creation techniques using metal materials, particularly stainless steel, provides opportunities for artists and designers to explore unique and aesthetically valuable organic curves, especially in functional objects such as furniture, interior accessories, public sculptures, and metal crafts. These biomorphic forms are chosen because they differ from common geometric shapes and can create visual appeal. This research aims to explore the application of the SMAW welding technique on stainless steel rods to create three-dimensional artworks with organically inspired forms. The study employs a practice-based research method, combining direct practice with result analysis to generate new knowledge. The technique used is Shielded Metal Arc Welding (SMAW), which utilizes heat from an electric arc between a shielded electrode and the base metal to melt and fuse the materials into a solid alloy. In this research, 4 mm diameter stainless steel rods were used as the primary material, and the process included preparation, welding execution, grinding, polishing, documentation, and practice-based analysis. The findings demonstrate the successful application of the SMAW technique in forming betta fish fins with organic curve characteristics. This work proves that practice-based research is an effective approach for generating artistic and design innovations through material and technique exploration. This research contributes to the development of experimental material-based metal crafts and enriches contemporary art discourse by creating original works through the innovative application of the SMAW welding technique to stainless steel rods in producing complex three-dimensional organic forms, such as betta fish fins, which have rarely been explored in previous studies.